(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1991)
The stratigraphic and paleogeographic analysis of the Carnian-Norian boundary succession in central Lombardy allows the recognition of a new unit, the Castro Formation. This unit, 100-250 m thick, is represented by carbonatic intraformational breccias and associated limestones. Two lithozones have been recognized in the Castro Fm.: the lower one, heteropic with the S.Giovanni Bianco Fm., with dark dolomitic limestones and breccias intercalations, and the upper lithozone, massive, with amalgamated calcareous breccias. Microfacies, recrystallized and often tectonized, consist of mudstones, wackestones and fine packstones, locally rich in ostracods. Geochemical analyses show differences between the Castro Fm. and the overlying and underlying units, possibly because of early diagenetic meteoric imprint. The Castro Fm. depositional setting is represented by coastal ephemeral lakes with periodic emersions and erosional, tectonically controlled phenomena in a monsoonal regime.